Palladium‐Catalyzed Pyrazole‐Directed sp3 C−H Bond Arylation for the Synthesis of β‐Phenethylamines. (24th February 2017) - Gulia, Nurbey; Daugulis, Olafs
Abstract: We have developed a method for palladium‐catalyzed, pyrazole‐directed sp 3 C−H bond arylation by aryl iodides. The reaction employs a Pd(OAc)2 catalyst at 5–10 mol % loading and silver(I) oxide as a halide‐removal agent, and it proceeds in acetic acid or acetic acid/hexafluoroisopropanol solvent. Ozonolysis of the pyrazole moiety affords pharmaceutically important β‐phenethylamines. Abstract : Verbinden, um zu spalten : Eine Palladium‐katalysierte, Pyrazol‐dirigierte Arylierung von C(sp 3 )‐H‐Bindungen durch Aryliodide wurde entwickelt, die einen Pd(OAc)2 ‐Katalysator und Silber(I)‐oxid als halogenbindendes Reagens und Basenvorstufe nutzt. Die Ozonolyse der Pyrazolgruppe liefert pharmazeutisch wichtige β‐Phenethylamine.